Design and experiment of miss-seeding detection and preparatory seed scraper-belt compensation mechanism based on improved YOLOv5s for potato seed-metering devices - Li, Hongling; Zhang, Hua; Liu, Xiaolong; Li, Hui; Jia, Shangyun; Sun, Wei; Wang, Guanping; Feng, Quan; Yang, Sen (Frontiers in Plant Science, 2025)
This study addresses the issue of miss seeding in spoon-chain potato seed-metering devices, which impacts planting efficiency and quality, by proposing a miss-seeding detection and compensation system based on an improved YOLOv5s model integrated with a preparatory seed scraper-belt compensation mechanism. The enhanced model incorporates the Convolutional Block Attention Module (CBAM) and Soft Non-Maximum Suppression (Soft-NMS), achieving a mean average precision (mAP) of 99.40% in complex field environments. The system combines visual recognition with mechanical compensation. Experimental results demonstrate that at operating speeds of 0.2–0.4 m/s, the original miss-seeding rate of 5.28%–9.40% is reduced to 0.70%–1.68%, with a reseeding success rate of 82.14%–86.67% and a preparatory seed reseeding success rate exceeding 96%. The study validates the system’s efficiency and reliability under medium-low speeds, with slight performance degradation at higher speeds due to vibrations. This solution offers an intelligent upgrade path for traditional potato seed-metering devices and advances precision agriculture technologies.